Unnecessity of Routine Dissection of Right Central Lymph Nodes in cN0 Papillary Thyroid Carcinoma Located at the Left Thyroid Lobe - Zhang, Songtao; Zhang, Runfang; Wang, Chao; Gong, Wenbo; Zheng, Chen; Fang, Qigen; Dai, Liyuan (Frontiers in Oncology, 2021)
Objective The lymph node posterior to the right recurrent laryngeal nerve (LN-prRLN) is an important part of the central lymph nodes (LNs). We aimed to explore the rate and predictors of LN-prRLN metastasis in cN0 papillary thyroid carcinoma (PTC) located at the left thyroid lobe. Methods Patients with surgically treated primary left lobe PTC were retrospectively enrolled. The metastatic distribution of LN-prRLN and postoperative complications were assessed. The association between LN-prRLN metastasis and clinicopathological variables was evaluated by univariate and multivariate analyses. Results A total of 857 patients were included for the analysis. Central LN metastasis was noted in 310 (35.3%) cases. The most (27.6%) and least (1.7%) commonly involved LNs were the left paratracheal LN and the LN-prRLN. In the univariate analysis, the tumor size, multifocality, the extent of extrathyroidal extension (none vs. macroscopic vs. macroscopic maximal), and perineural invasion were associated with positive LN-prRLN. In the multivariate analysis, tumor size of >40.0 mm and macroscopic maximal invasion were found as the only two independent predictors. Transient and permanent hypoparathyroidism were noted in 90 (10.2%) and 13 (1.5%) patients, respectively. Voice change was noted in 40 (4.6%) patients, and 20 patients recovered. Conclusions In cN0 PTC located at the left lobe, LN-prRLN metastasis was very uncommon. We found that LN-prRLN dissection is not required routinely, but should be performed if the tumor size is >40.0 mm and macroscopic maximal extrathyroidal extension is present.